Editorial Perspective: Another look at 'optimal outcome' in autism spectrum disorder. (30th June 2022) - Eigsti, Inge‐Marie; Fein, Deborah; Larson, Caroline
Abstract : This paper addresses the hypothesis that autism spectrum disorder features follow multiple long‐term developmental trajectories, including an absence of symptoms that were present in childhood, by the time of adolescence. In early work on this topic, this circumstance was called an 'optimal outcome'. To better reflect the reality of multiple excellent outcomes regardless of whether autism spectrum disorder features are present or absent, including autonomy, daily living skills, communication skills, and relationships and employment/activities outside the home, the terminology 'loss of autism diagnosis' (LAD) has been proposed as a substitute. The paper also contextualizes an LAD outcome within research, practice and advocacy.